IMPLEMENTASI FUNGSI MANAJEMEN KURIKULUM PEMBELAJARAN MUATAN LOKAL PROGRAM KEPESANTRENAN DI SMP PLUS DARUSSALAM - Moh Nur Fauzi; Azmi Faizatul Qoyyimah (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2022)
This research is motivated by the National Education Standards for SD/MI as a study material in this learning activity which refers to PP RI No.19 of 2005 Education Standards. Its scope includes content standards; process standards; graduate competence standards; standards of educators and education personnel; standards of educational facilities and infrastructure; management standards; financing standards; and educational assessment standards. And also Law Number 20 of 2003, of which states that the curriculum is prepared in accordance with the level of education within the framework of the Republik of Indonesia, including the demands for religious knowledge. The purpose of this study was to determine the process of planning, organizing, implementing, and evaluating the curriculum and local content learning at SMP Plus Darussalam. By applying three models of data analysis, namely: Data Reduction, Data Display, Conclusion Drawing, and Verification. Therefore this research was carried out at SMP Plus Darussalam which has an Islamic Boarding School program. This research is descriptive-analytic qualitative research. The method of data collection is done by documentation, observation, and in-depth interviews. The results of this study indicate that: Curriculum planning in improving the local content learning program at SMP Plus Darussalam, Organizing local content learning in the Islamic boarding school program at SMP Plus Darussalam, and Implementing the curriculum in improving the content learning program. The local content at SMP Plus Darussalam includes the implementation of local content learning for the Islamic boarding school program which consists of PAI, Aswaja, and the Qur’an. the form of curriculum evaluation in improving the learning of local content of the Islamic boarding school program at SMP Plus Darussalam.